Immunopathological features of early age cancer: microsatellite instability in colorectal cancer - Zaborowski, Alexandra (Trinity College Dublin. School of Biochemistry & Immunology. Discipline of Biochemistry, 2023)
Title: Immunopathological features of early age cancer: microsatellite instability in colorectal cancer Background and hypothesis Deciphering the interplay between tumour biology and the immune system may aid the design of novel immunotheraputic strategies and identify patients who would derive a meaningful benefit from immunotherapy. It is hypothesised that tumour biology influences the immune response in colorectal cancer and that early age onset disease is associated with distinct immunopathological features in comparison to late onset disease. Specific aims Aim 1: To evaluate the immunopathological features of microsatellite instability in early age onset colorectal cancer Aim 2: To evaluate inhibitory checkpoint expression on tumour-infiltrating lymphocytes according to microsatellite status Results Aim 1: Four retrospective observational studies were conducted. For colon cancer, tumour budding and BRAF/KRAS mutations are more common in patients with microsatellite instability. The rate of nodal positivity is comparable to those with microsatellite stable tumours. For rectal cancer, patients with microsatellite instability are less likely to be node positive and more likely to achieve a complete pathological response to neoadjuvant therapy. Aim 2: A prospective study was conducted to evaluate inhibitory checkpoint expression on tumour-infiltrating lymphocytes by flow cytometry. PD-1 expression was significantly increased in tumours with microsatellite instability however, one in four microsatellite stable tumours had comparable levels of PD-1 expression. Expression varied significantly among patients with the same microsatellite status. Microsatellite instability in isolation may not accurately predict response to immunotherapy with checkpoint blockade. Conclusion The immune response represents an important therapeutic target in colorectal cancer.
APPROVED
Keywords: Colorectal cancer; Microsatellite instability